Validation of a Portable Force Plate for Evaluating Postural Sway. Issue 1 (February 2021) - Walsh, Mark; Church, Caroline; Hoffmeister, Audrey; Smith, Dean; Haworth, Joshua
Measurements of postural sway are used to assess physiological changes due to therapy or sport training, or to describe group differences based on activity history or disease status. Portable force plates have been widely adopted for this purpose, leading us in this study to validate with linear and nonlinear metrics the posturographic data derived from both a portable plate (Natus) when compared to an in-ground plate (Bertec). Twenty participants stood on each plate for two trials each, with and without a foam perturbation and with and without eyes open on each surface. We calculated measures of path length, range, root mean squares, sample entropy, and correlation dimensions from center of pressure traces on each plate. An intraclass correlation coefficient across trials from each plate in each condition indicated satisfactory overall reliability (ICC consistency), supporting the use of either plate for postural sway research and interventions. Additionally, our results generally supported common validity (ICC absolute agreement), though, the specific degree of similarity differed for each of the tested metrics of postural sway, especially when considering whether or not data was filtered. For situations in which participants cannot visit a laboratory (e.g. performing athletes, community dwelling clinical patients, and virus risk concerns) an in-home portable force plate is a trusted and valuable data collection tool.